Alcohol taxation and regulation in the European Union - Sijbren Cnossen (Center for Economic Studies and ifo Institute (CESifo), 2006)
This paper estimates the external costs of harmful alcohol use in the European Union (EU) and confronts them with the alcohol excise duty collections per adult and per litre of pure alcohol in the various Member States. In all but one Member State, drinkers do not appear to pay their way. This reflects the EU's acquiescence in a formidable alcohol problem. Fifteen per cent of adults drink too much', while the extent of youth drinking has reached alarming proportions. The external costs should be internalised in price through an appropriate optimal alcohol excise duty, supplemented by regulatory measures aimed at specific problem groups. Further, a coordinated alcohol tax policy seems called for, which would, among others, raise the minimum duties on wine, beer and spirits, preferably in line with their relative alcohol content. A drawback of these measures is that they would reduce the welfare of moderate drinkers.
Keywords: H2; H8; 330; Alkoholsteuer; Alkoholpolitik; Alkoholkonsum; Soziale Kosten; EU-Staaten